Inequality and growth in Portugal: a reappraisal for the period 1986-2017 - Fernandes, Miguel (2022)
This paper investigates the inequality-growth nexus for Portugal over the period 1986-2017. Portugal is a country that has recorded a decelerating growth trajectory together with high levels of inequality, coupled with relatively low levels of human capital and productivity. We compute different measures of earnings inequality using microdata from the Quadros de Pessoal database and use them to estimate VAR and SVAR A-B models with four variables (human capital, inequality, investment and output) to empirically assess the sign of the relationship between inequality and growth, as well as the underlying mechanisms. The results from the impulse response analysis indicate that a shock to inequality has a negative impact on growth and on human capital availability, and an initial negative impact on investment which eventually becomes positive. The evidence found highlights the human capital, savings, and domestic demand channels as good candidates to explain the relationship between inequality and growth in Portugal.